Incidence of psychrotrophs bacteria with potential public health implications in ice cream sold in Zakho markets - AlBany, Yousif Abdulla; Mohammed, Reem Qasim; Azzo, Nagham Mohammed; Al-Berfkani, Mohammad Ismail (International Journal of Research in Medical Sciences, 2017)
Background: Foodborne illness are caused by the consumption of food that is contaminated with either bacteria or their toxins and the most common causes are psychotropic bacteria which cause major public health problem. The aim was to detect and enumerate pathogenic bacteria in locally made ice cream. Methods: 250 locally made ice cream samples were randomly collected from automatic soft machines and dipping cabinets in the markets of Zakho city over a period of ten months starting in July 2016 to May 2017. All collected samples were transported to the microbiology laboratory. The most probable number methods used for detection and enumeration of pathogenic psychotropic bacteria. Results: In general, both types of ice cream samples were showed heavy contamination with aerobic bacteria. The Staphylococcus aureus (MRSA) counts exceeded the standard limits in all samples; the count in dipping cabinets’ samples was higher than automatic soft machines samples whereas Coliform count in automatic soft machines samples was higher than dipping cabinets’ samples. High incidence of Salmonella and Listeria monocytogenes had been detected in all ice cream samples and the range in samples from automatic soft machines were higher than samples obtained from dipping cabinets. Conclusions: This study indicates a high prevalence of pathogenic psychrotrophs in unpacked ice cream and poor hygiene during production, which make local ice cream unsuitable for consumption and it is indicating the need to monitor the hygienic quality of markets and the health authorities must be informed about such cases to avoid food poisoning.